A CRITICAL ANALYSIS OF AN EMERGING CRISIS OF THE INDIAN AGRICULTURAL DOMAIN CITING THE EQUIVOCAL FARM BILLS (2020) - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi; Devi Manoharmayum, Dolpriya (International Journal of Psychosocial Rehabilitation, 2022)
"Circumstantial research indicates that competitive market conditions are comparatively lesser than the prescribed minimum support prices (MSPs). Farmers scare that corporate production would result in lower prices." - Kunal Kundu, an Indian Economist, Societe Generale. Despite all bountiful income tax exemptions and government subsidies, farmers have been languishing over the years because of low yield costs, demonetization, ever-increasing expenses, and overall dearth. Many farmers have become indebted, which has brought about an expansion in farmer suicides as of late. Down to this, the Indian Government has passed confrontational laws such as "1. Farmers’ Produce Trade and Commerce (Promotion and Facilitation) Act, 2020; 2. Farmers (Empowerment and Protection) Agreement on Price Assurance and Farm Services Act 2020; and 3. Essential Commodities (Amendment) Act, 2020," which would disintegrate a portion of the statutes that have ensured India’s farmers for quite a long time and subject them to unbound, unrestricted economic campaigns with high competition. The media reports also stipulated the bills, which did not specify anything about MSP. Subsequently, many farmers, generally from the northern provinces of Punjab and Haryana, have congregated in Delhi, claiming to withdraw these three farm acts. As reported by the news wire, the farmers who are protesting need support from every sphere of the country. For instance, MSPs are the Government’s security net that prices fall for explicit yields, predominantly wheat and rice. Farmers would be guaranteed to pay a convinced rate notwithstanding economic situations, and government organizations would buy a portion of those yields at that cost. The trepidation is that if MSPs are dispensed with, big corporates may set costs that further disfavor farmers. However, the Indian Government has expressed that MSPs and government procurement would not return. Furthermore, protesting farmers need the Government to ensure MSPs for their harvests.